Perancangan dan Pembuatan Sistem Informasi Administrasi Klinik Paripurna Surya - Patric Avidjaja Roseli; Adi Wibowo; Silvia Rostianingsih (Jurnal Infra, 2017)
Currently Solar Plenary Clinic in recording medical records still use a medical card. Surya Plenary Clinic’s recording medical records, laboratory examinations and prescriptions are still manual. Information system will make all data recording faster in data processing and archiving more secure and automatically stored properly.This application is created using the programming language HTML, PHP, Javascript, jQuery and MySQL database. App view using SB Admin and Bootsrap template. This application can record medical records, lab checks, doctor prescriptions, drug requests, drug stock logs and reports. Admin may view required reports such as medical record transaction reports, laboratory transactions reports, patient reports and illnesses, incoming drug reports. This report can make it easier for admins to monitor clinical progress.The end result of this application development for all recording and inspection can be well integrated and with the assessment of the questionnaire can ensure the application has been tested and in accordance with the needs of the clinic.